Business study mission (Western Canada) business and the environment - Suan, Hwee Feng (2010)
Geographically, Canada is susceptible to the detriments of global environmental problems such as the accumulation of toxic chemicals, climate changes, ozone depletion and loss of bio-diversity. Recognising its vulnerability, Canada has been actively championing the preservation and protection of the environment both domestically and internationally.